Inter-disciplinary approaches to international law: Legal & non-legal rituals for genocide survivors - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Legal processes, however powerful and authoritative they might be, are not cure-alls. Case in point: victims of the Khmer Rouge regime in Cambodia are still seeking healing and closure thirty years on. While the international tribunal might be able to hold the perpetrators accountable, there is a disconnect between what this international legal procedure can achieve, and what the victims want, notes SMU law professor Mahdev Mohan. To help the victims, he said non-legal actions are needed.